Elucidating heavy metals ions detection using screen printed electrodes with starch carbon dots as modifier - Subramaniam, Sathya Rau; Zainal Abidin, Zurina; Issa, Mohammed Abdullah; Harun, Nur Haninah; Pudza, Musa Yahaya (Springer Nature, 2025)
Modified electrodes can produce significant improvement to detection of heavy metal. This is particularly useful especially in detecting similar characteristics heavy metal like same outer valence cations which can be challenging due to small signal difference. This study aims to investigate the effectiveness of screen printed electrode modified with starch carbon dots. Cyclic voltammetry measurements were conducted between –1.0 to + 1.0 V at a scan rate of 200 mV/s in 0.5M acetic acid solution for sensing Zn(II) and Cu(II) at concentration range of 0.5 to 10 ppm and 0.25 to 5 ppm respectively. Morphology, functional groups, particle size distribution and surface charges analysis were done for further elucidation. Results showed enhanced electron-transfer kinetics and current intensity for the modified electrode with carbon dots. Detection Limits of 0.122 ppm and 0.089 ppm for Zn(II) and Cu(II) was recorded under optimum conditions with excellent repeatability. Testing on spiked samples which consisted of distilled water, electrolyte and heavy metals, gave and excellent recoveries of the zinc and copper of more than 90%wt recovery. Although Zn(II) and Cu(II) are divalent cations of same group, their interactions with CDs on electrode surface for sensing still produce detectable differing signals due to difference in atomic size, charges, electron number and their molecular structures. Based on above mentioned characterization, CV performance and reliability testing, the modified SPE-CDs is capable to produce reliable detection of heavy metals with similar valency number in aqueous solution.